2013
DOI: 10.1016/j.bpj.2013.03.021
|View full text |Cite
|
Sign up to set email alerts
|

The Ebola Virus Matrix Protein Deeply Penetrates the Plasma Membrane: An Important Step in Viral Egress

Abstract: Ebola virus, from the Filoviridae family has a high fatality rate in humans and nonhuman primates and to date, to the best of our knowledge, has no FDA approved vaccines or therapeutics. Viral protein 40 (VP40) is the major Ebola virus matrix protein that regulates assembly and egress of infectious Ebola virus particles. It is well established that VP40 assembles on the inner leaflet of the plasma membrane; however, the mechanistic details of VP40 membrane binding that are important for viral release remain to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(126 citation statements)
references
References 52 publications
5
120
0
Order By: Relevance
“…However, the majority of this previous work predated knowledge on purification conditions and mutations that may influence VP40 dimer, monomer, or octameric ring structure. In fact, previous work from the Stahelin lab using a GST-VP40 expression system with subsequent cleavage of the GST tag (13,20) demonstrated purification of monomeric VP40 identified by chemical crosslinking (E. Adu-Gyamfi and R.V. Stahelin, unpublished data).…”
Section: Generation Of Evp40 Conformational Mutantsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, the majority of this previous work predated knowledge on purification conditions and mutations that may influence VP40 dimer, monomer, or octameric ring structure. In fact, previous work from the Stahelin lab using a GST-VP40 expression system with subsequent cleavage of the GST tag (13,20) demonstrated purification of monomeric VP40 identified by chemical crosslinking (E. Adu-Gyamfi and R.V. Stahelin, unpublished data).…”
Section: Generation Of Evp40 Conformational Mutantsmentioning
confidence: 99%
“…A number of earlier studies have examined the role of PS in lipid vesicle binding and cellular assembly of VP40 demonstrating an important role for PS in membrane binding and membrane curvature changes (13,19,20,31,32) as well as a critical requirement of plasma membrane PS levels in VLP formation (27). However, the majority of this previous work predated knowledge on purification conditions and mutations that may influence VP40 dimer, monomer, or octameric ring structure.…”
Section: Generation Of Evp40 Conformational Mutantsmentioning
confidence: 99%
See 2 more Smart Citations
“…This suggested that perhaps an L-domain in one of the other viral proteins may be contributing or possibly VP40 may achieve scission without the aid of the host cell. To the credit of the latter hypothesis, VP40 alone has been shown to mediate budding and scission into synthetic vesicles recapitulating plasma membrane lipid composition [30,31]. However, it was revealed recently that VP40 possesses a third L-domain, a YPxL/I motif , which has been shown to mediate interactions with the early ESCRT protein Alix [12••].…”
Section: How Does Virus Particle Scission From the Plasma Membrane Ocmentioning
confidence: 99%